Nesporazumi s četrto vejo oblasti - Žerdin, Ali (Podjetje in delo, 2016)
In non-reflected discussions the press is often labelled as "fourth branch of government". The label is unfortunate metaphor that causes deep misunderstandings. Label is wrong from the constitutional and legal perspective, from the perspective of political philosophy and also from the perspective of historical analysis. Print in is an important pillars of social power, but this pillar collapses into itself.
Keywords: delitev oblasti; družbena moč; družbeni nadzor; država; množični mediji; oblast; tisk